Cross border SMEs: Malaysia & Indonesia - Abdullah, Moha Asri (UMY Press, 2020)
Much have been written in various forms with respect to Micro, Small and Medium Enterprises (MSMEs). In spite of this, a compilation of articles “cross border SMEs”, especially between Malaysia and Indonesia, has still not been made available to the public. Prior to addressing the issue at hand, let us look at what we mean by MSMEs for Malaysia and Indonesia? Micro, Small and Medium Enterprises (MSMEs) have been defined differently in both countries. So far, there has not been a unified definition that is accepted by all. In Malaysia, SME Corp, a coordinating body on SMEs, refers to micro size SMEs as companies with sales turnover of less than RM300,000 and employees less than five. However, for small size SMEs in the manufacturing sector, it refers to companies that have sales turnover between RM300,000 and RM15 million and employees between 5 and 75 people, while in the services sector it is described as companies that have sales turnover between RM300,000 and RM3 million, and employees between 5 and 30 people. As for medium size SMEs, in the manufacturing sector, it includes companies with sales turnover between RM15 million and 50 million, and employees between 75 and 200 people. However, in the services sector, companies that have sales turnover between 15 million and RM 20 million and employees between 30 and 75 people are already considered as medium size SMEs. In Indonesia, MSMEs are defined as those enterprises which have full time employment of less than 100 employees with a substantial proportion of them consisting of micro enterprises with not more than five full-time employees. Elsewhere in these two nations, SMEs are much regarded as “unsung heroes” as they play significant economic and social roles by offering new job opportunities, lowering unemployment rate, increasing competition and productivity, and providing substantial benefits to the economy of the two countries, Malaysia and Indonesia alike. The SMEs in both the neighboring nations are considered to be the backbone of the modern-day economy. Thus, it is far from being a surely not a “fish bone” anymore. The importance of this segment is undisputed. For instance, a total of 98.5 percent of the Malaysian business establishments are SMEs. In 2017, these businesses were responsible for 37.1 percent of the country’s GDP, 66 percent the total employment of the country, and 17.3 percent of the total Malaysian export. The annual growth of these SMEs’ contributions towards the GDP, employment and export are 7.2 percent, 3.4 percent and 7.9 percent respectively. A more or less similar example can be illustrated for the Indonesian counterpart. The importance of MSMEs in the Indonesian national economy has been well noted. There are more than 56.8 million MSMEs establishments and they consist of approximately 99.9 percent of the total number of enterprises. It can be further emphasized that within MSMEs, micro-enterprises seem to be more dominant compared to small and medium enterprises. It covers about 98.7 percent, while small and medium enterprises represent only about 1.13 percent and 0.09 percent respectively.